2021
DOI: 10.1186/s12886-021-02168-y
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma and its predictors among adult patients attending ophthalmic outpatient department: a hospital-based study, North West Ethiopia

Abstract: Background Nearly 1.9% of global blindness is caused by glaucoma and this is sadly high in Africa which is around 15% and In Ethiopia, glaucoma is responsible for 5.2% of blindness. It is also the fifth cause of blindness in Ethiopia. Scarce information is available regarding glaucoma in Ethiopia; hence we determined the proportion of glaucoma and its associated factors in North West Ethiopia which will be utilized for future related researches and different stakeholders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
2
1
Order By: Relevance
“…The proportion of glaucoma subjects in our glaucoma service seems higher (45%) compared to other hospital-based studies in Nigeria (18.2%),[ 18 ] Ethiopia (26%),[ 19 ] and Ghana[ 20 ] and lesser than that reported by Das et al . [ 21 ] from the north of India (70%).…”
Section: Discussioncontrasting
confidence: 71%
“…The proportion of glaucoma subjects in our glaucoma service seems higher (45%) compared to other hospital-based studies in Nigeria (18.2%),[ 18 ] Ethiopia (26%),[ 19 ] and Ghana[ 20 ] and lesser than that reported by Das et al . [ 21 ] from the north of India (70%).…”
Section: Discussioncontrasting
confidence: 71%
“…However, the others are employee (14%), farmer (7%), student (5%), teacher (1%) and saler (1%). Wubet et al reported that concerning occupational status, 39 (15.6%) of farmers had glaucoma and 91 (30.6%) had no glaucoma [28]. In the current study we found that 60% of participants were self-reported history of glaucoma and 44% weren't self-reported history of glaucoma.…”
Section: Glaucoma Sub-types Of Studied Patientssupporting
confidence: 43%
“…32%), respectively while 13 (19.7%) of them had secondary glaucoma[28].Khandelwal et al illustrated that the distribution of glaucoma by subtype in the current study indicated that the majority of cases have primary open angle glauco-ma (POAG)[36]. In study of Singaporean Chinese conducted by Baskaran et al PO-AG comprised 47% of glaucoma cases[27].…”
mentioning
confidence: 44%
“…2,5 There is little research on the scope and contributing variables of MCS among glaucoma patients despite the higher prevalence of glaucoma and prevalent mental illnesses among glaucoma patients in Ethiopia. [17][18][19] Additionally, studies conducted in Africa and other regions of the world indicate that the magnitude of MCS is substancially high among glaucoma patients, and that there are significant differences between the reported magnitude of MCS among glaucoma patients in Africa and other regions of the world.…”
Section: Introductionmentioning
confidence: 99%